Migraine related white matter lesions in the differential diagnosis of multiple sclerosis: Magnetic resonance imaging features - Fatih Yetkin, Mehmet (Annals of Medical Research, 2021)
Aim: This study aims to describe the lesion characteristics of conventional magnetic resonance imaging (MRI) of patients who are directed to a university hospital with a pre-diagnosis of demyelinating disease who are finally diagnosed as MrWMLs.Material and Methods: Individuals who were referred to an MS outpatient clinic of a university hospital with a pre-diagnosis of demyelinating disease and finally diagnosed with migraine according to the International Classification of Headache Disorders (ICHD) -3 (β) criteria who also have MrWMLs and 45 age and gender-matched individuals who are diagnosed with MS according to the 2017 McDonald diagnostic criteria, without migraine-type headache were retrospectively analyzed. Results: Forty-five individuals with migraine and 45 age and gender-matched individuals who are diagnosed with MS were included. The median time since diagnosis was 10 (0.5-32) years for the migraine group and 5 (0.3-20) years in the group with MS (p=0.031). The median age of the group with migraine was 35 (23-54) years, while the median age of the group with MS was 34 (20-55) years. There was no significant difference between the groups in terms of average age and gender distribution (p=0.342 and p=0.389). The total number of T1 and T2 lesions were significantly higher in the MS group. Similarly, the number of infratentorial and periventricular lesions was higher in the MS group (p0.001). The number of deep white matter lesions was higher in the migraine group (p0.05).Conclusion: In this study, conventional MRI tips were defined for differentiating MS lesions from MrWMLs which has an important place in the differential diagnosis of MS. MrWMLs were deep white matter lesions that are predominantly located at the frontal and parietal lobes. Studies involving more individuals and using automated segmentation software may provide more information to differentiate MrWMLs from MS lesions.
Keywords: Multiple sclerosis; migraine; white matter lesions